Diurnal spider diversity in Balugo Watershed, Salvacion, Tacloban City - Romero, Jeremy B. (2019)
Spiders are ubiquitous organisms that feed mainly on insects, making them proficient insect-controller, and indicator for anthropogenic stress. This study focused on the diurnal spider fauna of Balugo Watershed, Salvacion, Tacloban City, Leyte which was sampled to assess the diversity, evenness and relative abundance. Three 50x50-m plots was established and sampling was done following conservation-oriented biodiversity rapid assessment protocol. A total of 129 individuals from 18 species representing 6 families were captured. The most abundant spider family was Family Araneidae with Agelena labyrinthica as the most abundant species. Overall, the species were variably distributed with a moderate level of species diversity (H1= 2.705). Majority of the species were found in Plot A due to the complexity caused by human-mediated modifications which provided increased habitat complexity and prey abundance. The data is enough evidence to conclude that Balugo Watershed in Salvacion, Taclobban City can still support spider fauna and diversity, but regular follow-up studies of wider scope are needed to further assess the spider fauna in the area.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.